1998
DOI: 10.1111/j.1572-0241.1998.00288.x
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Ciprofloxacin in the Prevention of Bacterial Infection in Patients With Cirrhosis After Upper Gastrointestinal Bleeding

Abstract: Prophylactic intestinal decontamination with oral ciprofloxacin is effective in the prevention of bacterial infections in patients with cirrhosis who were suffering from acute upper gastrointestinal hemorrhage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
76
0
5

Year Published

2002
2002
2015
2015

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 125 publications
(86 citation statements)
references
References 28 publications
5
76
0
5
Order By: Relevance
“…3,4,[17][18][19] The high efficacy of GVO, with either a single or double dose, for arresting active bleeding was shown by the finding that more than 90% of bleeding was arrested, which again is consistent with our findings and with those of previous studies. [5][6][7][8][9][10][11] The rebleeding rate was 8.8% higher in group A with a number needed to treat of approximately 11, which may be considered of potential clinical importance.…”
Section: Discussionsupporting
confidence: 95%
See 1 more Smart Citation
“…3,4,[17][18][19] The high efficacy of GVO, with either a single or double dose, for arresting active bleeding was shown by the finding that more than 90% of bleeding was arrested, which again is consistent with our findings and with those of previous studies. [5][6][7][8][9][10][11] The rebleeding rate was 8.8% higher in group A with a number needed to treat of approximately 11, which may be considered of potential clinical importance.…”
Section: Discussionsupporting
confidence: 95%
“…27 Bacteremia should have been reduced in the era of routinely used prophylactic antibiotics in patients with acute variceal bleeding. 17,18 The 30-day mortality and survival rates were no different between groups. More than half of them died of liver failure, which is mostly dependent on hepatic reserve, and this variable was equally distributed between groups.…”
Section: Discussionmentioning
confidence: 91%
“…70 Ciprofloxacin has the advantage over the majority of fluoroquinolones because it is well-tolerated with low hepatotoxicity, which had been used to effectively prevent bacterial infection in patients with cirrhosis after upper gastrointestinal bleeding. 70,71 The same study also observed an inhibition of the activated hepatic endocannabinoid system in ciprofloxacin-treated cirrhotic animals, which enhanced the concepts of endotoxemia and activate hepatic endocannabinoid system in cirrhosis. 11,58,70 Actually, chronic administration of the cannabinoid receptor antagonist inhibits the hepatic inflammation and fibrogenesis in cirrhotic animals.…”
Section: (4) Endocannabinoidsmentioning
confidence: 64%
“…Many clinical trials proved that prophylactic antibiotics with oral norfloxacin, intravenous ciprofloxacin, or ceftriaxone in cirrhotic patients with gastrointestinal (GI) bleeding can reduce infections and mortality [2][3][4][5]. Previous studies showed that enteric aerobic Gram-negative bacteria (GNB) are the most common causative organisms in patients with acute hemorrhage [2,3,[6][7][8]. However, there are some epidemiological changes in the etiology of infections because Gram-positive cocci (GPC) have markedly increased in cirrhotic patients, probably due to more invasive procedures in treating liver diseases in recent years [5].…”
Section: Introductionmentioning
confidence: 99%